Subchapter S, an entrepreneurial survival strategy for small banks - Steven G. Craig; Polly T. Hardee (The Journal of Entrepreneurial Finance and Business Ventures, 2002)
With the passage of the Small Business Job Protection Act of 1996, many small banks throughout the United States became eligible to reorganize as a Subchapter S corporation. This allows these banks to eliminate double taxation, and increase shareholder value. Consequently, employing this entrepreneurial survival tool extends new life to the small bank. Accompanying this strategy are differences in corporate governance, primarily more concentration of ownership. Thus, this paper examines the behavior of Subchapter S banks as compared to banks of similar size in order to determine significant performance differences. It also focuses on bank structure and small business lending activity, an area of high asset concentration in small banks. Overall, we find shareholder value appears to increase in a Subchapter S banking organization through higher earnings, larger dividend payout ratios, and similar risk measures. We find little differences in these banks in relation to small business lending. The implications are that a small bank's survival rate will be higher in the consolidation process by employing the Subchapter S strategy.
Keywords: 650